Characterizing the chemical composition of red coloring matter samples from the Altamira cave using synchrotron µXRF imaging - Tapia, José; Eveno, Myriam; Prada, Alfredo; Fatás, Pilar; de las Heras, Carmen; Arias, Pablo; Müller, Katharina; Schöder, Sebastian; Reiche, Ina (Applied physics. A, Materials science & processing, 2024)
The chemical in situ study of red coloring matter from Paleolithic cave art is challenging because the same trace elements can be present both in the matter and in the calcitic support, and the two present a heterogeneous composition. In this study, thirteen red iron oxide-based coloring matter samples obtained at drip points coming from eight locations within the Techo de los Polícromos , Altamira cave (Spain), have been analyzed by highly sensitive synchrotron-induced micro-X-ray fluorescence (SR-µXRF). Our analyses improved the characterization of red Paleolithic pigments by establishing characteristic trace element patterns, additionally facilitating a comparison of the distinct representations within the cave. Furthermore, new differentiation criteria between the composition of the calcitic walls and that of the red coloring matter could be established, helping to improve future non-invasive analyses.